Implementation of HOTS in English Learning with a Dayak Cultural Approach and a Christian Religious Education Perspective at Kuala Kapuas - Berth Penny Pahan; Al Egi (Fakultas Keguruan dan Ilmu Pendidikan Kristen IAKN Palangka Raya, 2026)
This study examines the implementation of Higher Order Thinking Skills (HOTS) in English learning through a Dayak cultural approach and a Christian Religious Education perspective at State Senior High Schools and Vocational High Schools in Kuala Kapuas. It is based on the assumption that students are still in the adaptation stage of applying higher-order thinking and often experience difficulties in responding to analytical, evaluative, and creative tasks. This research employed a qualitative descriptive method to provide a comprehensive picture of current practices in schools. Data were collected from English teachers and students. The findings indicate that teachers have implemented HOTS-based learning and assessment through various activities, including essay writing, multiple-choice questions, project-based learning, group discussions, and summarizing reading texts to develop speaking and reading skills. The integration of Dayak cultural values and Christian Religious Education perspectives supports contextual and meaningful learning, encouraging students to think critically and reflect on moral values. The Independent Learning Curriculum further strengthens the development of higher-order thinking skills, such as analyzing, evaluating, and creating. However, several challenges remain, including limited vocabulary mastery and insufficient instructional time, which affect the optimal implementation of HOTS in classroom practice.